Identificação e análise dos fatores de risco cardiovascular de professores da zona rural de um município do interior do Amazonas - Oliveira, Gemeson dos Santos (Brasil, 2025)
Introduction: The World Health Organization (WHO) has highlighted that cardiovascular diseases (CVDs) are the leading cause of global death, resulting in approximately 17.9 million deaths annually. The Pan American Health Organization (PAHO) considered CVDs to be the leading cause of mortality in the Americas region. The report emphasized that most fatalities occur in low- and middle-income countries, and that risk factors related to these conditions include symptoms such as chest pain, shortness of breath, fatigue, and palpitations. Objective: to identify and analyze the cardiovascular risk factors of rural teachers in a municipality in the interior of Amazonas. Methods: Consisted of a cross-sectional exploratory study carried out in July 2023, involving 100 rural teachers, selected based on specific criteria, and with ethical approval. Results: The majority of participants were female (61%), with a mean age of 42 years. We observed a high prevalence of risk behaviors, such as sedentary lifestyle and inadequate diet, and anthropometric analysis revealed overweight, especially among men. Inactivity time was high, reducing the risk of increased CVDs. The discussion emphasizes that, although the rural environment may favor physical activity, professional demands lead to sedentary patterns, worsening cardiovascular health. Conclusion: This study revealed the vulnerability of teachers in Coari/AM to cardiovascular diseases, linked to socioeconomic factors and a sedentary lifestyle, with a high prevalence of overweight and occupational stress. Limited access to healthcare exacerbates the situation. The findings are crucial for developing public policies that promote prevention, access to healthcare, physical activity, and psychosocial support for these professionals.